THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND ENGAGEMENT IN LEARNING ACTIVITY USING ChatGPT - Nyimas Eka Dewi; Sunarti; Ibrahim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research explores the correlation between students' motivation and engagement in learning activities using ChatGPT, an AI-based interactive tool. It focuses on how ChatGPT influences students' intrinsic and extrinsic motivation, as well as their behavioral, emotional, and cognitive engagement. A quantitative correlational design was employed, involving 385 students from Universitas Muhammadiyah Kalimantan Timur selected through simple random sampling. Data were collected using a validated Likert-scale questionnaire based on Self-Determination Theory and Fredricks’ engagement framework. The results indicated that students demonstrated moderately high levels of motivation (M = 29.65) and high levels of engagement (M = 32.52) when learning with ChatGPT. Spearman’s rho analysis revealed a moderate and statistically significant correlation (ρ = .559, p < .01) between motivation and engagement. These findings suggest that higher levels of motivation are associated with increased engagement in AI-supported learning activities. The study concludes that ChatGPT can effectively enhance both motivation and engagement, offering practical insights for educators and curriculum designers in developing more interactive, personalized, and student-centered learning experiences. Integrating ChatGPT into educational contexts supports the advancement of digital pedagogy and promotes more meaningful learning in 21st-century classrooms.